Exploring Programmatic Issues which Affect Continuing Legal Education in Kansas - Holly B Fisher; W. Franklin Spikes (Adult Education Research Conference, 2017)
This mixed methods research study identified common mandatory continuing legal education (MCLE) practices by Kansas providers and evaluated these against established adult and continuing education best practices.
Keywords: Continuing Legal Education; Mandatory Continuing Legal Education; Continuing Professional Education